Active Disturbance Rejection Fuzzy Controller for Roll Stabilization of Autonomous Underwater Vehicle under Wave Disturbance. (20th April 2015) - Wang, Lin-Lin; Wang, Hong-Jian; Pan, Li-Xin; Guo, Jun-Xi
Abstract : Considering the case of autonomous underwater vehicle navigating with low speed near water surface, a new method for designing of roll motion controller is proposed in order to restrain wave disturbance effectively and improve roll stabilizing performance under different sea conditions. Active disturbance rejection fuzzy control is applied, which is based on nonlinear motion model of autonomous underwater vehicle and the principle of zero-speed fin stabilizer. Extended state observer is used for estimation of roll motion state and unknown wave disturbance. Wave moment is counteracted by introducing compensation term into the roll control law which is founded on nonlinear feedback. Fuzzy reasoning is used for parameter adjustment of the controller online. Simulation experiments on roll motion are conducted under different sea conditions, and the results show better robustness improved by active disturbance rejection fuzzy controller of autonomous underwater vehicle navigating near water surface.